Accuracy of Using Meta AI in Defining the Methods of Nahwu I'rab Based on Jurumiyah Book - Utari, Zeli; Alrasi, Fitri; Bambang, Bambang (Universitas Muhammadiyah Sumatera Barat, 2025)
This study uses a qualitative method with a literature study to analyze the accuracy of the meaning of i'rab and its types from the Jurumiyah Book using Meta AI. This method involves collecting data from various literature and written sources to understand the accuracy and suitability of the translation by Meta AI. Data collection is carried out by observation and documentation, then with accuracy and data analysis to obtain in-depth knowledge about the use of technological advances in learning, especially Arabic language learning. Based on this study, it is concluded that although the approach is different from the Jurumiyah Book, Meta AI can provide the meaning of the rules of nahwu i'rab science flexibly, precisely and easily understood. Meta AI which is designed in a modern way provides a more descriptive picture and is accompanied by examples that are increasingly easy to understand. While the Jurumiyah Book is more formal and concise. Both sources agree on the basic principles of Arabic grammar. Thus, Meta AI can be used as one of the reference sources in learning, especially for learners who want more practical, concise and easy-to-understand information.